Performance Improvement of CH3NH3PbI3 Perovskite Solar Cell by CH3SH Doping - Hong Li; Yingguo Yang; Xiao Feng; Kongchao Shen; Haiyang Li; Jiong Li; Zheng Jiang; Fei Song (Nanomaterials and Nanotechnology)
Organometal halide perovskites have recently emerged as an appealing candidate in photovoltaic devices due to their excellent properties. Therefore, intense efforts have been devoted to find the ideal organics for perovskite solar cells. In response, we investigate the doping effect of CH3SH organic on the structure and related performance of a CH3NH3PbI3 perovskite solar cell, via in situ synchrotron- based grazing incidence X-ray diffraction (GIXRD), together with scanning electron microscopy (SEM). In situ GIXRD investigations clearly illustrated the transformation and modification of the perovskite structure induced by the organic dopant, which subsequently led to the enhance‐ ment of the power conversion efficiency of fabricated solar cells. Notably, nanoporous morphology and nanocrystal‐ line structures were discovered in the perovskite film by SEM; they were also confirmed by the increase in broad‐ ening peaks/features in the GIXRD measurements. Overall, our study may ultimately result in an attractive strategy for the fabrication of high performance perovskite solar cells.